Changes in land cover resulting from the introduction of non‐native pine modifies litter traits of temperate forests in Patagonia. (13th February 2020) - Franzese, Jorgelina; Raffaele, Estela; Blackhall, Melisa; Rodriguez, Johanna; Soto, Alejandra Y.
Abstract: Aims: Changes in land cover resulting from the introduction of non‐native pine plantations and subsequent pine invasion is increasingly affecting forest areas in the Southern Hemisphere, and having negative impacts on diverse ecosystem components. We studied the abundance, biophysical attributes, and flammability of litter in temperate forests modified by the introduction of the non‐native Pinus radiata, and later by its post‐fire invasion from adjacent sites. We also evaluated the short‐term effects on litter of mechanical removal of P. radiata from post‐fire invasion sites. Location: North‐western Patagonia, Argentina. Methods: We measured abundance, depth, moisture content and determined species composition of litter samples collected at native forest, plantation, and post‐fire invasion and removal sites. We also performed flammability tests on leaf litter samples of the dominant species from each habitat type. In all cases, litter traits from the modified habitats were compared with those obtained from native forest (reference system). Results: Moisture content and litter species composition were notably affected by the alteration of habitat. A decrease in species richness and changes in the identity and abundance of the dominant species were the most remarkable shifts recorded in the modified habitats. While pine needles were mainly associated with parameters indicative of high leaf litter flammability, the opposite was found for leaves of the dominant native trees. The removal of invasive pines from early post‐fire invasion did not reveal any biophysical changes in litter that would indicate a tendency towards the conditions found in native forest litter. Conclusions: Pine needles as a novel element in litter found in pine‐dominated habitats have a prominent impact on litter traits associated with alterations in key ecosystem properties in comparison with the reference system. For a short‐term recovery of burned, invaded areas, additional ecological practices other than the removal of invasive trees should be conducted to successfully drive successional changes towards conditions similar to those found in native vegetation. Abstract : The introduction of non‐native pine plantations and subsequent pine invasion is increasingly affecting areas of natural forest in the Southern Hemisphere. We found that pine needles (as a novel element in the litter of the modified habitats) have a negative impact on species composition, quality and flammability of litter – changes that represent increased degradation and fire risk for the area.